2022
DOI: 10.5114/pq.2020.102163
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prediction rule validity to identify individuals with recurrent low back pain

Abstract: IntroductionOne set of clinical prediction rules (CPR) can be used clinically to identify patients with low back pain who are likely to benefit from motor control exercise. Individuals with a history of recurrent low back pain during remission (rLBP) still have persisting impaired trunk neuromuscular control. Accordingly, CPR should detect these individuals with rLBP. This study aimed to determine the predictive validity of CPR to identify individuals with rLBP.MethodsOverall, 30 subjects aged less than 40 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Research has found that the 1-year incidence of first ever low back pain episode ranges from 6.3% to 15.4%, while the 1-year incidence of recurrent low back pain episodes ranges from 24% to 80% 2 . The prevalence of low back pain during a person's life has been established at around 70-80% 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that the 1-year incidence of first ever low back pain episode ranges from 6.3% to 15.4%, while the 1-year incidence of recurrent low back pain episodes ranges from 24% to 80% 2 . The prevalence of low back pain during a person's life has been established at around 70-80% 3,4 .…”
Section: Introductionmentioning
confidence: 99%